Strategi Pemberdayaan Madrasah Hidayatut Thulab Melalui Pelatihan Kelembagaan di Desa Wagir Lor - Ibnu Khaeshin; Wahyu Hanafi Putra (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This community service program was motivated by the low quality of institutional management and learning at Madrasah Diniyah Takmiliyah Awwaliyah Hidayatut Thulab in Wagir Lor Village, characterized by limited facilities, simple organizational structure, and lack of varied teaching methods. The aim of this program is to empower the madrasah through institutional training to make it more structured, sustainable, and relevant to local needs. The method applied was Asset Based Community Development (ABCD), which consists of the stages of discovery, dream, design, and destiny. The results indicate that implementing ABCD has strengthened organizational and administrative structures, improved teachers’ teaching competence, increased community support, and enhanced students’ learning motivation. Thus, the ABCD-based empowerment strategy offers a sustainable solution for improving the quality of madrasah institutions in rural areas.